What sustainable road transport future? Trends and policy options - Stef Proost; Kurt Van Dender (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
A brief review of long run projections of demand for road transport suggests that problems related to road network congestion and greenhouse gas emissions are likely to become more pressing than they are now. Hence we review, from a macroscopic perspective, popular policy measures to address these problems: stimulating modal shift, regulating land use to reduce car use, and boosting low carbon technology adoption to reduce greenhouse gas emissions. We find that these policies can produce tangible results, but that they may have unintended consequences that drive up costs considerably.
Keywords: D62; Q54; R41; R48; 330; transport; environment; modal choice; climate change; car technology; Straßenverkehr; Nachhaltigkeit; Straßenverkehrspolitik; Verkehrsökologie; Verkehrsteilung; Kraftfahrzeugtechnik